PANCASILA AS A SOCIAL ETHICS SYSTEM AS A MORAL FOUNDATION IN A MULTICULTURAL SOCIETY - Lukman Hakim; Suranto Suranto (JUNAGARA: Jurnal Ilmiah Hukum dan Kenegaraan, 2025)
This study aims to analyze the implementation of Pancasila as a social ethical system and moral foundation in a multicultural society through educational practices at SMP Muhammadiyah 7 Bayat Klaten. The research employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, questionnaires, and document analysis involving the principal, teachers, and students. The findings reveal that Pancasila values have been integrated into classroom learning, school culture, and students’ social interactions. Approximately 94% of students demonstrate inclusive religious attitudes, 88% reflect tolerance in social relations, 86% actively participate in class deliberations, and 83% perceive fairness in task distribution and rule enforcement. These findings indicate that Pancasila functions as a social ethical system that shapes behavioral patterns, strengthens social cohesion, and maintains harmony within the multicultural school environment. The study concludes that continuous value reinforcement and critical reflection are necessary to ensure that Pancasila becomes deeply rooted as a moral foundation for the younger generation in facing the dynamics of modern society.